ANIMASI 2D MEDIA PEMBELAJARAN JARINGAN ORGAN TUBUH MANUSIA BERBASIS MOBILE - Nur Budi Nugraha; Soni fajar Mahmud (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
Learning is a process of communication between students, teachers and teaching materials. The delivery of learning messages from teachers to students is currently still using teaching aids in the form of books. This makes students less interested and feel bored when absorbing lessons, so that it gives the effect of being lazy to learn. This study designed mobile based 2D animation as an interactive learning tool for learning materials for human organs based on mobile android. This study uses the waterfall method in conducting research which includes the stages of planning, analysis, design, implementation and testing. Based on the research results, this 2D animation learning media makes it easy for students to study material about human organs that cannot be seen directly. This animation has several elements such as text, audio, video and animated images so that it attracts students' attention to feel happy in learning compared to conventional ways